Indígenas evangélicos y diversidad cultural. Análisis de una problemática multiculturalista (2018)
ABSTRACT: This article examines the ruling of the Constitutional Court of Colombia where this national institution authorized several sanctions imposed by the traditional authorities of the Arhuaco ethnic group against indigenous evangelicals who wish to practice their religion freely within their reserve. The arguments of the Court are carefully analyzed, considering that, although the Court intends to protect ethnic and cultural diversity, it also authorizes the expulsion of the evangelical Arhuacos. The concepts used by the Constitutional Court are compared with recent anthropological and sociological theories regarding subjects such as identity, cultural boundaries, inter-ethnic relations, and religion. It is concluded that, while the ideal of protecting ethnic and cultural diversity is not questionable, the state institution has relied on notions that need to be re-evaluated.